Danger after dark - McDonald, Ellie (Texas Annie's Attic/DRG Publishing, 2005)
Two friends investigate a strange light burning in an abandonned mansion.
Keywords: Friendship -- Juvenile fiction; Detective and mystery stories; Mystery fiction